2002
DOI: 10.1080/000163502753740124
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and predictors of young adults' perceived ability to cope with dental life events

Abstract: The purpose of the present study was to assess coping skills and predictors of the ability to cope with dental life events employing a 10-item rather than a 48-item rating questionnaire. A representative random sample of 1490 subjects aged 25 years from 3 Norwegian counties received a mail questionnaire in March 1997. The response rate was 62% after 1 reminder. Eight selected items from the Social Readjustment Rating Questionnaire (SRRQ) plus 2 dental items were presented as graphic rating scales with the endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Thus two thirds of the respondents claimed to have visited a dentist regularly, at least once a year, during the last 5 years, and 81% reported three or more visits during this period. Further support for this notion is provided by the fact that Norwegian adults find it relatively difficult to cope with the loss of teeth and getting dentures (40, 41). Another possible explanation for the comparatively modest impact of personal and family income on dental status may be that 65% of adults, who had visited a dentist during the last 12 months had paid 1500 NOK (∼US$ 225) or less (42), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus two thirds of the respondents claimed to have visited a dentist regularly, at least once a year, during the last 5 years, and 81% reported three or more visits during this period. Further support for this notion is provided by the fact that Norwegian adults find it relatively difficult to cope with the loss of teeth and getting dentures (40, 41). Another possible explanation for the comparatively modest impact of personal and family income on dental status may be that 65% of adults, who had visited a dentist during the last 12 months had paid 1500 NOK (∼US$ 225) or less (42), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, the CFSS‐SF scale, being a modification to the CFSS‐DF scale, was chosen as the measurement instrument for dental anxiety in children because it was shorter and had high reported reliability (9,14). It has been shown that shorter rating questionnaires are generally more acceptable to children (15) and that the CFSS‐SF can successfully be applied, particularly in the African situation (9).…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been shown that over‐ and underestimation tend to balance each other out at group level (32). Secondly, Norwegian adults find it relatively difficult to cope with losing one or more teeth (24, 33), a fact that ought to enhance the reliability of these self‐report findings. Furthermore, Gilbert et al.…”
Section: Discussionmentioning
confidence: 99%
“…The questions had fixed response alternatives. Pre‐testing was deemed unnecessary because the questions were simple, pertained to issues which the public are able to answer reliably (10, 18–21), and had been used without difficulties before (22, 24).…”
Section: Methodsmentioning
confidence: 99%